Philipp Waldeck diary - Waldeck, Philipp, 1750-1784.; Burgoyne, Bruce E. (1776)
Typewritten transcription and translation of a diary kept by Waldeck while chaplain with the 3rd English-Waldeck Regiment (Waldeckische Regiment, 3te, of the principality of Waldeck) during the American Revolution. Documents military events in New York, New Jersey, and Florida and voyages from Germany to New York (October 1776) and from New Jersey to West Florida via Jamaica (October 1778). Includes Waldeck's observations on social life and environment of Indians in West Florida, slaves in Jamaica, German Americans, and others.
Transcript, in part.
Typewritten transcript and translation from the handwritten copy of original field diary. Handwritten copy is in New York Public Library's Bancroft Collection.
Hessian chaplain serving as a mercenary with the British forces. Full name: Johann Philipp Franz Elissaus Waldeck.
Collection material in German transcription, with English translation by Bruce E. Burgoyne.
Keywords: Waldeck (Fürstentum). -- Waldeckische Regiment, 3te.; German Americans; Indians of North America -- West Florida; Slavery -- Jamaica; Voyages and travels; Florida -- Description and travel; Florida -- History -- Revolution, 1775-1783.; Germany -- Description and travel; Jamaica -- Description and travel; New Jersey -- Description and travel; New Jersey -- History -- Revolution, 1775-1783.; New York (State) -- Description and travel; New York (State) -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783 -- Chaplains; United States -- History -- Revolution, 1775-1783 -- Participation, German; Chaplain, Hessian; Hessian mercenaries